An exploratory study of differences between a functionally infertile, an organically infertile and a fertile group of married couples on the dimensions of interactional functioning and mutual perceptions between partners - Futeran, Elizabeth Lora (Department of Psychology, 2016)
Bibliography: pages 142-149.